Ellipse described with little information

Geometry Level 4

Let S S be the focus of an ellipse.Let the latus rectum of the ellipse through S S intersect the ellipse at P P and Q Q .Tangents to the ellipse at points P P and Q Q intersect at a point R R .

Given that Q R P = 6 0 \angle QRP = 60^\circ , find the eccentricity of the ellipse.

Submit your answer to three decimal places.


The answer is 0.577.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

If angle QRP = x x , then e = tan ( x / 2 ) e = \tan (x/2) , where e is the eccentricity of the ellipse.

I'll post the complete solution later.

See my full solution above, Harsh!

tom engelsman - 3 months, 3 weeks ago
Tom Engelsman
Feb 21, 2021

Let the ellipse be x 2 a 2 + y 2 b 2 = 1 \frac{x^2}{a^2}+\frac{y^2}{b^2}=1 with focus S ( a 2 b 2 , 0 ) S(\sqrt{a^2-b^2},0) and latus-rectum endpoints P ( a 2 b 2 , b 2 a ) , Q ( a 2 b 2 , b 2 a ) P(\sqrt{a^2-b^2}, \frac{b^2}{a}), Q(\sqrt{a^2-b^2}, -\frac{b^2}{a}) . If P R Q = π 3 \angle{PRQ} = \frac{\pi}{3} (with R R on the x x- axis by symmetry), then the slope of tangent P R = tan ( π / 6 ) = 1 3 PR = -\tan(\pi/6) = -\frac{1}{\sqrt{3}} and Q R = tan ( π / 6 ) = 1 3 . QR = \tan(\pi/6) = \frac{1}{\sqrt{3}}.

WLOG, let us focus on tangent P R PR . If we differentiate the ellipse at P P , we obtain:

d y d x x = a 2 b 2 = b a x a 2 x 2 b a a 2 b 2 a 2 ( a 2 b 2 ) = 1 3 \frac{dy}{dx}|_{x=\sqrt{a^2-b^2}} = -\frac{b}{a} \cdot \frac {x}{\sqrt{a^2-x^2}} \Rightarrow -\frac{b}{a} \cdot \frac{\sqrt{a^2-b^2}}{\sqrt{a^2-(a^2-b^2)}} = -\frac{1}{\sqrt{3}} ;

or a 2 b 2 a 2 = 1 3 b 2 = 2 3 a 2 . \frac{a^2-b^2}{a^2} = \frac{1}{3} \Rightarrow b^2 = \frac{2}{3}a^2.

The ellipse's eccentricity is finally computed per:

e = a 2 b 2 a = ( 1 2 / 3 ) a 2 a = 1 2 / 3 = 1 3 . e = \frac{\sqrt{a^2-b^2}}{a} = \frac{\sqrt{(1-2/3)a^2}}{a} = \sqrt{1 - 2/3} = \boxed{\frac{1}{\sqrt{3}}}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...